Grandparents' involvement in providing care for their preschool aged grandchildren - Reyes, Jennel Drezza Fe C.
The study aimed to find out the extent of involvement grandparents have in taking care of their preschool aged grandchildren; to identify the childcare tasks and activities grandparents do for and with their grandchildren; and to provide an understanding on how grandparents get involved in providing childcare. Twenty grandparents of preschool aged grandchildren from Quezon City were interviewed, and data were analyzed using content analysis. Five case studies were done to show in-depth of their involvement. Three types of grandparents' nature of childcare involvement emerged from the study: grandparents who volunteered their help, grandparents whose help was requested, and grandparents whose assistance was assumed by grandchildren's parents. Data gathered show that parents provided care to help parents who are both working. Grandparents were found to do various childcare tasks and activities for/with their grandchildren. These were done by most grandparents three to five times a week while weekends were reserved for the grandchildren's parents. Further studies can look into the grandchildren's parents' perspective regarding the grandparents' childcare involvement.